The Arts-Based Research' approach: hints for educational research - Monica Pentassuglia (Firenze University Press, 2016)
The last two decades have seen a growing interest on the different ways of knowing in all the fields. Although some research has highlights the importance of this topic, there is still very little scientific understanding about this process. The first serious discussions and analyses of the construction of knowledge emerged during the 1900s. In Humanities field, questions have been raised about the use of traditional research paradigm considered unable for the understanding of these complex subjects. In this perspective, this article provided an important opportunity to advance the understanding of new research paths that not only overturn the classical perspective of research, but also allow us to reformulate and reinvent strategies, tools, and forms of representations of research findings. This article considers the implications of the approach of Arts-Based Research (ABR) and deeply of dance-based methods for educational research. L'approccio dell'Arts-Based Research: quali spunti per la ricerca educativa? Tra i temi che più si sono imposti, negli ultimi anni, all'attenzione dei ricercatori, è il problema dei processi di costruzione della conoscenza ad aver catalizzato su di sé la maggior parte degli studi; è soprattutto in ambito umanistico che cresce l'idea secondo cui i classici paradigmi di ricerca non siano in grado di comprendere ed indagare la complessità dei fenomeni esplorati. Sulla scia di tali necessità, il presente contributo intende approfondire l'approccio dell'Arts-Based Research (ABR) ed in particolare dei dance-based methods nel campo della ricerca educativa che negli ultimi anni sta contribuendo a capovolgere l'impostazione classica del processo di ricerca a favore di nuovi percorsi in grado di utilizzare le potenzialità dell'Arte secondo nuove prospettive.